Gut–lung axis: role of the gut microbiota in non-small cell lung cancer immunotherapy - Zhang, Huaiyuan; Xu, Ziyuan (Frontiers in Oncology, 2023)
Immunotherapy for non-small cell lung cancer (NSCLC) has advanced considerably over the past two decades. In particular, immune checkpoint inhibitors are widely used for treating NSCLC.However, the overall cure and survival rates of patients with NSCLC remain low. Therefore, continuous investigation into complementary treatments is necessary to expand the clinical advantages of immunotherapy to a larger cohort of patients with NSCLC. Recently, the distinctive role of the gut microbiota (GM) in the initiation, progression, and dissemination of cancer has attracted increasing attention. Emerging evidence indicates a close relationship between the gut and lungs, known as the gut-lung axis (GLA). In this review, we aim to provide a comprehensive summary of the current knowledge regarding the connection between the GM and the outcomes of immunotherapy in NSCLC, with particular focus on the recent understanding of GLA. Overall, promising GM-based therapeutic strategies have been observed to improve the effectiveness or reduce the toxicity of immunotherapy in patients with NSCLC, thus advancing the utilization of microbiota precision medicine.